Economy and administration. A diachronic look on return to its essence: the human being (2019)
The article seeks to approach the reflection that in consideration of the economic and administrative disciplines has been made about the human beingfrom some representative authors in these fields of knowledge. The paper presents a diachronic view and tries to leave open the reflection about the conception of the human in economic and organizational perspective. The phenomenon allows us to reveal the presence of a changing humanism from historicalreflection, characterized by the particular context and contingencies of the moment, which has generated opening and possibilities of questioning discoursesand practices historically, not counting on a specific regional context. In thesubject of the human, from the economy and the administration has given aproblematic of sense and hierarchy of its imperatives, that where it seems totake meaningful advantage individualism in consideration of collective socialdevelopments